2018
DOI: 10.1016/j.yclnex.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Model-based analysis of postprandial glycemic response dynamics for different types of food

Abstract: Results: We collected a large range of postprandial glucose and insulin dynamics for 53 common food products and mixed meals. Currently available glycemic measures were found to be inadequate to describe the heterogeneity in postprandial dynamics. By estimating model parameters from glucose and insulin data, the physiology-based dynamic model accurately describes the measured data whilst adhering to physiological constraints. Conclusions: The physiology-based dynamic model provides a systematic framework to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 51 publications
(72 reference statements)
0
25
0
Order By: Relevance
“…Previous studies have repeatedly described variability of postprandial plasma levels of different enteroendocrine factors such as glucose and insulin (Hall et al, ; Zeevi et al, ). Interestingly, these studies have highlighted an association between high postprandial glycemic variability and cardiometabolic risk (Hall et al, ; Jung, ), emphasizing the relevance of postprandial variability for metabolic health and thus the need for better quantification and analysis of postprandial variability (Rozendaal et al, ). High interindividual variability of postprandial bile concentrations is reported in the literature (Al‐Khaifi et al, ; Eggink et al, ; Fiamoncini et al, ; Sonne et al, ; Steiner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have repeatedly described variability of postprandial plasma levels of different enteroendocrine factors such as glucose and insulin (Hall et al, ; Zeevi et al, ). Interestingly, these studies have highlighted an association between high postprandial glycemic variability and cardiometabolic risk (Hall et al, ; Jung, ), emphasizing the relevance of postprandial variability for metabolic health and thus the need for better quantification and analysis of postprandial variability (Rozendaal et al, ). High interindividual variability of postprandial bile concentrations is reported in the literature (Al‐Khaifi et al, ; Eggink et al, ; Fiamoncini et al, ; Sonne et al, ; Steiner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we must emphasize that in the work of Zeevi et al, the study group consisted of a healthy population and it should be confirmed that the findings are equally valid in people with diabetes before they can be used to optimize the diabetes treatment. Recently, Rozendaal et al demonstrated that the large variability in postprandial glycemic response dynamics to different types of food is inadequately predicted by existing glycemic measures such as the Glycemic Index, the Glycemic Load and the Glycemic Glucose Equivalents [52]. They quantitatively described the postprandial glycemic response dynamics using a physiology-based dynamic model.…”
Section: Inter-subject Variability Of a Response To Mealsmentioning
confidence: 99%
“…These examples are interesting in that they can be used to predict the dose and timing of nutrient arrival in the blood stream in response to a given food or a meal, and could be easily connected with nutritional models that aim to predict the metabolic fate and consequences of absorbed amino-acids [12], lipid products [13], or sugars [14] in the fed state. However, to build a PBK model of food transit and absorption that becomes truly relevant for predictive purposes, there remains a clear need to more directly relate the properties of the foods or meals with: (i) the kinetics of enzymatic hydrolysis, and (ii) the GI transit, in particular the gastric emptying kinetics.…”
Section: Introductionmentioning
confidence: 99%